2011
DOI: 10.1007/s10142-011-0213-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses of winter barley to cold indicate nucleosome remodelling as a specific feature of crown tissues

Abstract: We report a series of microarray-based comparisons of gene expression in the leaf and crown of the winter barley cultivar Luxor, following the exposure of young plants to various periods of low (above and below zero) temperatures. A transcriptomic analysis identified genes which were either expressed in both the leaf and crown, or specifically in one or the other. Among the former were genes responsible for calcium and abscisic acid signalling, polyamine synthesis, late embryogenesis abundant proteins and dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 94 publications
(137 reference statements)
2
48
0
3
Order By: Relevance
“…In fact, the cold acclimatisation process in barley has been mainly studied from a genomic and transcriptomic point of view. Transcriptional responses of winter barley to various periods of low (above and below zero) temperatures were recently evaluated by Janská et al (2011). Their results interestingly revealed that during the cold acclimation process, the production of ice nucleation substances in both the leaf and the crown was suppressed, correlating with the rapid up-regulation of genes encoding the major antifreeze (chitinases, glucanases, thaumatin-like proteins) and ice recrystallization inhibition proteins.…”
Section: Analysis Of the Barley Proteome Under Lt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the cold acclimatisation process in barley has been mainly studied from a genomic and transcriptomic point of view. Transcriptional responses of winter barley to various periods of low (above and below zero) temperatures were recently evaluated by Janská et al (2011). Their results interestingly revealed that during the cold acclimation process, the production of ice nucleation substances in both the leaf and the crown was suppressed, correlating with the rapid up-regulation of genes encoding the major antifreeze (chitinases, glucanases, thaumatin-like proteins) and ice recrystallization inhibition proteins.…”
Section: Analysis Of the Barley Proteome Under Lt Stressmentioning
confidence: 99%
“…Likewise, Wang et al (2004) found a close correlation between levels of antifreeze proteins (CLP and TLP) and degrees of freezing tolerance and it has been revealed that the expression of antifreeze genes is significantly induced by cold acclimation. In addition, during the cold and sub-zero acclimation various heat-shock proteins (HSPs) were also induced in the leaf (Janská et al, 2011). Moreover, in this tissue cold acclimation resulted in the up-regulation of sucrose degradation enzymes, whereas, in the crown, the induction of the expression of sucrose transporter genes, rather than those of the sucrose degradation machinery, was observed.…”
Section: Analysis Of the Barley Proteome Under Lt Stressmentioning
confidence: 99%
“…Metabolite fingerprints to cold stress were obtained for Drosophila melanogaster individuals (Korn et al, 2010) and showed that the strategies to cold adaptation might be the same within all members of the kingdom. Janská et al (2011) confirmed all the significant metabolic variations, stirring in cold acclimatization, reenforcing the impression that the combination of cryoprotectant molecules is of great valve (Guy et al, 2008). Amongst these cryo-protectans, sugars, sugar alcohols and proline were exposed to be of higher significance.…”
Section: Metabolomics Profiling In Crop Plantsmentioning
confidence: 54%
“…Janská et al (2011) also observed only a marginal effect of low temperature on the expression of genes involved in sucrose/starch metabolism in the crown of winter barley. They hypothesized that sucrose can be exported rather than cleaved into fructose and glucose, as the few genes that were significantly upregulated in the crown were indeed sucrose transporters.…”
Section: Discussionmentioning
confidence: 90%
“…Ss2 was expressed in the endosperm only, whereas Ss1 mRNA was expressed in both roots and leaves (Martinez de Ilarduya et al, 1993). Sucrose synthase activity increases during cold acclimation in leaves (Crespi et al, 1991;Sasaki et al, 2001;Janská et al, 2011). In wheat exposed to low temperature, Ss1 activity was found to be higher in the winter wheat cultivar Monopol than in the spring wheat cultivar Katepwa (Savitch et al, 2000).…”
Section: Introductionmentioning
confidence: 95%